CLASSICAL ARABIC POETRY CATEGORIZATION USING N-GRAM FREQUENCY STATISTICS - Mohammad, Iqbal (Iraqi Journal of Science, 2024)
Most of the Arabic language vocabulary is built from the roots derivation. These roots are words composed of three to five consonants letters. Any performance in Arabic language for the purpose of information retrieval needs to deal with the language morphological and structural changes first (which is called the stemming process) then a statistical method for extracting information is implemented. This approach presents a method for categorizing the Classical Arabic Poetry (CAP) into its categorizations: Ghazal, Medeh, Wasef, Hijaa',..etc. by combining the algorithm of a light stemmer (which identify sets of prefixes and suffixes in an Arabic word in order to reach to the word root after removing the suffixes and prefixes) with "N-gram" statistical method (which retrieves the information independently of the language complexity). Two measures will be implemented: the "Manhattan distance" dissimilarity coefficient and the "Dice's measure" similarity coefficient for the purpose of categorization.